The regulatory role of microRNAs in breast cancer - Loh, Hui Yi; Norman, Brendan P.; Lai, Kok Song; Nik Abd Rahman, Nik Mohd Afizan; Mohammed Alitheen, Noorjahan Banu; Osman, Mohd Azuraidi (MDPI, 2019)
MicroRNAs (miRNAs) are small non-coding RNA molecules which function as critical post-transcriptional gene regulators of various biological functions. Generally, miRNAs negatively regulate gene expression by binding to their selective messenger RNAs (mRNAs), thereby leading to either mRNA degradation or translational repression, depending on the degree of complementarity with target mRNA sequences. Aberrant expression of these miRNAs has been linked etiologically with various human diseases including breast cancer. Different cellular pathways of breast cancer development such as cell proliferation, apoptotic response, metastasis, cancer recurrence and chemoresistance are regulated by either the oncogenic miRNA (oncomiR) or tumor suppressor miRNA (tsmiR). In this review, we highlight the current state of research into miRNA involved in breast cancer, with particular attention to articles published between the years 2000 to 2019, using detailed searches of the databases PubMed, Google Scholar, and Scopus. The post-transcriptional gene regulatory roles of various dysregulated miRNAs in breast cancer and their potential as therapeutic targets are also discussed.